Ketogenic diet in the treatment of drug-resistant epilepsy in children: Assessment of clinical efficacy, health care resource consumption, and direct medical costs - E.G. Lukyanova; A.G. Tolkushin; S.O. Ayvazyan; K.V. Osipova; E.A. Pyrieva; A.I. Krapivkin; V.A. Zhestkov (S.S. Korsakov Journal of Neurology and Psychiatry, 2026)
Objective. To evaluate the impact of the ketogenic diet (KD) on clinical outcomes, health resource consumption, including medication burden, hospitalization rates, and outpatient care, and direct medical costs (DMCs) in pediatric patients with drug-resistant epilepsy (DRE). Material and methods. A retrospective, non-interventional observational study was conducted at a specialized medical center. Data were collected from 58 children diagnosed with DRE: 29 patients received the ketogenic diet, while 29 patients comprised the comparison group. The clinical characteristics of epilepsy, frequency of seizures, efficacy of treatment, duration of the ketogenic diet, occurrence of adverse events, history of drug therapy, and the number of hospitalizations and outpatient consultations with a neurologist over two years were systematically evaluated. Based on the data obtained, the DMCs were calculated over 10 years. Results. The administration of the KD resulted in an average reduction of 83% in the number of epileptic seizures as compared to baseline (p=0.037) and a 78% decrease relative to the comparison group (p=0.013). The mean number of hospitalizations over two years was significantly lower in the KD group, with 2.70±3.22 hospitalizations compared to 10.14±7.79 in the comparison group (p=0.0001). Additionally, the number of consultations with a neurologist was markedly reduced (p=0.00001). By decreasing the consumption of health care resources — specifically, hospitalizations and outpatient neurological consultations — the DMCs over a ten-year horizon, excluding the cost of the ketogenic diet, were 3.05 times lower when utilizing the ketogenic diet; while maintaining observed trends in clinical efficacy, and taking into account the cost of the ketogenic diet, DMCs were reduced by approximately 130.000 rubles. The cost of antiepileptic medications accounted for a smaller share of DMCs, contributing 15% to overall expenditure. Conclusions. The application of the KD in children with DRE yielded favorable clinical outcomes, characterized by a significant reduction in seizure frequency, decreased consumption of health care resources, and financial savings on DMCs. These findings support the consideration of the KD as a clinically effective and cost-effective treatment approach compared to standard management practices for patients not receiving the KD.